Chute and Conduit-Tubular Carcinoma Breast - Bajaj Anubha (International Journal of Neonatology, 2024)
A brief case communication discusses a rare breast carcinoma subtype, summarizing pathology features, imaging, and considerations for surgical and adjuvant management.
Keywords: Tubular carcinoma